Construção e validação de instrumentos de avaliação psicossocial - Oliveira, Romero Cardoso (2024)
This thesis aims to propose and validate a psychosocial assessment questionnaire for work environments. To this end, it will be developed in the format of 4 articles. The first article aimed to analyze the use of the terms “psychosocial factors” and “psychosocial risks” in scientific publications. A review of psychosocial assessment articles was carried out and the definitions used in these articles were analyzed. The final sample included 79 articles and the results indicated that few articles cited definitions or concepts from the psychosocial field and a relationship between the use of a certain term and the focus of the article. The second article aimed to investigate the psychosocial assessment methods that are most used in studies in the psychosocial field today. A review of articles that used questionnaires to evaluate a certain work situation was also carried out. Thus, a final sample of 353 articles was collected, which provided a total of 25 different psychosocial assessment methods. These assessment methods were all questionnaires, from which all the questions were collected for subsequent analysis, making it possible to identify the psychosocial aspects that have been considered in psychosocial assessments at work, thus involving various factors related to the organization of work, internal and external factors work and psychological and cognitive factors. The third study aimed to carry out statistical validation of psychosocial assessment questionnaires developed in this study. For this, 4 studies were carried out, where study 1, using a sample of workers from a shoe industry, reduced the questions in the questionnaires, through a commonality analysis. In study 2, semantic validation of the final questionnaire was carried out, using a sample of workers from the Cleaning Services of a Federal Institute of Education. Studies 3 and 4 consisted of the exploratory and confirmatory factor analysis stages of the questionnaires, resulting in all questionnaires obtaining satisfactory statistical indices. As for the last article, the objective was to present the forms of psychosocial assessment of the proposed questionnaires, explaining how the questionnaires were applied, which is the main contribution of the tool to the assessment of psychosocial risks. Two studies then took place, of which study 1, carried out with workers from an industry, consisted of the application of seven individual questionnaires. In study 2, with teachers from a Federal Institute of Education, the questionnaires were administered in stages. In this case, the analyzes indicated that the categories “autonomy” and “planning and support” obtained better results in the evaluation of the first stage. The second stage confirmed, according to reports from workers, that “Risks at Work”, “Requirements and Satisfaction” and “Resources and Concerns” may be the factors that require attention and in-depth analysis to assess psychosocial risks in the workplace. work.